2018
DOI: 10.1111/cns.12865
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity strength and its correlations with cognitive function in subjects with ultra‐high risk for psychosis at rest

Abstract: Significantly altered FCS in the frontal-occipital network is observed in the UHR subjects. Furthermore, decreased FCS in the left middle frontal gyrus and increased FCS in the left calcarine have significant correlations with the cognitive measures of the UHR subjects and thus improve our understanding of the underlying pathophysiological mechanisms of schizophrenia. Moreover, a combination of the FCS values in the 2 brain areas can serve as a potential image marker to distinguish UHR subjects from healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 60 publications
(64 reference statements)
2
9
0
1
Order By: Relevance
“…Therefore, the combination of high VMHC values in the inferior frontal gyrus and posterior cingulate cortex, as well as in the inferior temporal gyrus and postcentral gyrus, may serve as a potential image marker to distinguish the patients with BSP from healthy controls. Our report is consistent with those of fMRI studies in patients with schizophrenia ( Li et al, 2018 ; Wang et al, 2018 ). Therefore, early detection and improved accuracy of the diagnosis in patients with BSP may be achieved based on the fMRI imaging using the combination of inferior frontal gyrus and posterior cingulate cortex or the inferior temporal gyrus and postcentral gyrus.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the combination of high VMHC values in the inferior frontal gyrus and posterior cingulate cortex, as well as in the inferior temporal gyrus and postcentral gyrus, may serve as a potential image marker to distinguish the patients with BSP from healthy controls. Our report is consistent with those of fMRI studies in patients with schizophrenia ( Li et al, 2018 ; Wang et al, 2018 ). Therefore, early detection and improved accuracy of the diagnosis in patients with BSP may be achieved based on the fMRI imaging using the combination of inferior frontal gyrus and posterior cingulate cortex or the inferior temporal gyrus and postcentral gyrus.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study found that prodromal individuals had altered functional connectivity strength (FCS) in the frontal‐occipital network. Furthermore, decreased FCS in the left middle frontal gyrus was significantly correlated with the cognitive measures in the prodromal individuals . Hence, correlations between increased GMV in the frontal lobes and clinical/cognitive parameters are expected in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, the combined assessment of BS and symptomatic UHR criteria might help to better understand brain imaging results in UHR samples reporting both GMV decrease (in the right gyrus rectus, the right superior frontal gyrus, and the left superior frontal gyrus) and GMV increase (in the bilateral median cingulate, the right fusiform gyrus, the left superior temporal gyrus, and the right thalamus) (56). The GMV-increased primary auditory and neocortical language regions, superior temporal gyrus, and insula were reported as the core regions responsible for the positive symptoms, such as delusions, hallucinations, and disorganized speech (57-59) and, in longitudinal studies, progressive GMV reduction of the superior temporal gyrus was linked to low improvement in positive psychotic symptoms (60,61). These GMV increases are still subject to debate and discussed in relation to different pathophysiological processes in the early phase, age, other demographic differences, genetic predisposal, and different MRI scanners or parameters employed in the method section (56).…”
Section: Discussionmentioning
confidence: 99%